2008
DOI: 10.1161/atvbaha.108.167999
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 Upregulation by Atheroprone Shear Stress Via p38-, α2β1-Dependent Mechanism in Endothelial Cells

Abstract: Objective-The initiation of atherosclerosis is in part dependent on the hemodynamic shear stress environment promoting a proinflammatory phenotype of the endothelium. Previous studies demonstrated increased expression of ER stress protein and unfolded protein response (UPR) regulator, GRP78, within all vascular cells in atherosclerotic lesions and its regulation in the endothelium by several atherosclerotic stressors; however, regulation of GRP78 by shear stress directly has not been established. Method and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 39 publications
5
64
1
2
Order By: Relevance
“…3B ). Previous reports have implicated endothelial ER stress as a relatively early event during atherogenesis (21)(22)(23). Quantifi cation of endothelial ERAI fl uorescence showed a prominent increase at 8 weeks ( Fig.…”
Section: Mice and Dietsmentioning
confidence: 69%
“…3B ). Previous reports have implicated endothelial ER stress as a relatively early event during atherogenesis (21)(22)(23). Quantifi cation of endothelial ERAI fl uorescence showed a prominent increase at 8 weeks ( Fig.…”
Section: Mice and Dietsmentioning
confidence: 69%
“…79 Indeed, ER stress is markedly increased in endothelial cells subjected to atherosclerosisprone shear stress. 80 Consistently, transcript profiles revealed that the most abundant feature of the endothelium of all atherosusceptible regions is the upregulation of genes associated with ER stress. 81 Dong et al demonstrated that the dysfunction of AMPK significantly increases the level of ER stress and suppresses sarcoplasmic reticulum calciumtransporting ATPase (SERCA) activity in endothelial cells.…”
Section: Atherosclerosismentioning
confidence: 77%
“…Endothelial ER stress was found in areas of disturbed flow in both swine (329) and mice (506). BiP (immunoglobulin heavy chain-binding protein, also known as GRP78), the best studied ER chaperone and mediator of ER stress, could be induced by exposing cultured endothelial cells to disturbed flow with upregulation dependent on MAPK p38 and integrin ␣ 2 ␤ 1 signaling (506).…”
Section: Er Stress In Endothelial Cellsmentioning
confidence: 99%